ANALISIS BERBAGAI PERAN PARA PIHAK DALAM KEMITRAAN PEMANFAATAN SUMBERDAYA MANGROVE - Sri Suharti (Pusat Penelitian dan Pengembangan Hutan, 2016)
ABSTRACTSectoral and administrative conflict in mangrove management along with the basic demand of human needs has lead to mangrove degradation and deforestation widely occurred in Indonesia. In order to increase its benefits while preserving the remaining mangrove forest, it is urged to execute painstaking effort and harmonious coordination among relevant stakeholders. This study aims to identify the role of stakeholders involved in mangrove partnership, describe interest and power of each stakeholder and formulate an alternative model of mangrove utilization partnership. The study was conducted in the northern coastal region of Central Java. Data were collected through observation, multi-stakeholder discussions and interviews with key informants and analyzed using qualitative descriptive analysis techniques. The results showed that stakeholders involved in the mangrove utilization partnership have diverse interests and influences. Primary stakeholders are Provincial and District Forestry Office, Department of the Environment, Department of Marine and Fisheries and mangrove forest communities. While secondary stakeholders consist of Universities/research institution, NGOs (local and Int'l), Private sector and village government. Establishment of partnership model should be able to manage various interests and power of stakeholders and utilize their existing potential power. Collaborative management model could be an alternative to be implemented to gain equitable distribution of benefits and responsibilities.Key words : Interest, power, social, economy, collaborativeABSTRAKKonflik antar instansi (sektoral) maupun antar wilayah (administratif) dalam pemanfaatan sumberdaya (SD) mengrove mengakibatkan penyusutan areal dan kerusakan mangrove secara luas dan masif di Indonesia. Untuk meningkatkan manfaat sekaligus melestarikan ekosistem mangrove yang masih tersisa perlu upaya nyata serta koordinasi yang harmonis antar pihak yang terkait (pemerintah, perguruan tinggi/lembaga riset, swasta, NGO dan masyarakat). Penelitian ini bertujuan untuk mengidentifikasi peran para pihak dalam kemitraan pemanfaatan mangrove, mendapatkan deskripsi tentang kepentingan dan pengaruh dari setiap stakeholder serta merumuskan alternatif pola kemitraan pemanfaatan mangrove. Penelitian dilakukan di wilayah pesisir utara Jawa Tengah. Pengumpulan data dilakukan melalui observasi, diskusi multi pihak dan wawancara kepada sejumlah informan kunci. Data dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa stakeholder yang terkait dalam kemitraan pemanfaatan mangrove memiliki kepentingan dan pengaruh yang beragam. Stakeholder primer adalah Dinas Kehutanan Provinsi, Dinas Perkebunan dan Kehutanan Kabupaten, Dinas Lingkungan Hidup, Dinas Kelautan dan Perikanan dan masyarakat sekitar hutan mangrove. Stakeholder sekunder terdiri dari perguruan tinggi, lembaga swadaya masyarakat (internasional dan lokal), swasta dan pemerintah desa. Inisiator kegiatan harus mampu mengelola kepentingan dan pengaruh stakeholder yang beragam serta memanfaatkan potensinya. Pengelolaan kolaborasi dapat menjadi model alternatif untuk diterapkan, sehingga terjadi distribusi manfaat dan tanggung jawab secara adil kepada semua stakeholder.Kata kunci : Ekonomi, kepentingan, kolaborasi, pengaruh, sosial